Rate of bloom of beef longissimus lumborum: effects of muscle temperature, age, and oxygen exposure time - Trater, C.M.; Hunt, Melvin C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Steaks from 12 loins were used to determine the best time and temperature combinations for blooming (development of a bright-red color) of the longissimus muscle at 2, 14, and 26 days postmortem. The lowest temperature (28°F) provided the fastest rate of bloom when the muscle was 2 days postmortem, and 30 minutes were needed to achieve 75% of final bloom color. For meat 14 days old, greater bloom occurred at 35 and 40°F than at 28°F. For meat 26 days old, rate of bloom was equal at all three temperatures. Thus, packers should bloom carcasses one-half hour at 28°F before presenting carcasses for grading, and retailers will need 30 to 40 minutes after cutting to achieve 75% of final bloom at 35° to 40°F.
Keywords: Beef; Longissimus lumborum; Muscle temperature; Muscle age; Muscle oxygen exposure time